Implementation of Religious Pluralism Tolerance in the Village of Penyangkringan, Kendal Regency - Haryono Haryono; Sri Suneki; Mahmud Yunus (JED (Jurnal Etika Demokrasi), 2023)
The pluralism of each region is different, both from ethnic variants, culture, language, and other supporting aspects. The purpose of this study was to analyze the pluralism of the community of Penyangkringan Village, Weleri District, Kendal Regency. This study uses a qualitative method with an ethnographic approach. Data collection tools using observation, interviews (in-depth interview and FGD), and documents. The data validity technique uses data triangulation, the analysis technique uses Spreadley qualitative analysis. The results of the study show that the implementation of tolerance for pluralism that exists in the community of Penyangkringan Village, one which is mutual respect for religious diversity. The positive impact of pluralism in Penyangkringan Village is the creation of a harmonious relationship between its residents as evidenced in cooperation activities (building gates, painting names of places of worship), road repairs, and community service. The community looks harmonious in various activities of religious and social life.